Pemberdayaan UMKM Melalui Pelatihan Pemasaran dan Branding Produk Era Digital - Damayanti, Putri Shela; Arifin, Muhammad Alwan Riza; Hermadiani, Firnanda; Ahmad, Azmi Fairuz (Welfare : Jurnal Pengabdian Masyarakat, 2025)
<!–StartFragment –> The digital era has become one of the most effective marketing tools for Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the role of social media in MSME product marketing strategies and its impact on increasing visibility and sales. Social media platforms such as Facebook and TikTok provide affordable and easily accessible platforms for MSMEs to build brands, interact directly with consumers, and creatively promote products. This community service program employed the ABCD (asset-based community development) method, employing five stages: discovery, dream, define, define, and destiny. The results of this activity demonstrate that the strategic use of social media can increase MSME competitiveness, expand market reach, and build stronger relationships with consumers. However, the effectiveness of this strategy is also greatly influenced by consistency, understanding of the target market, and the ability to manage content professionally. Thus, social media plays a vital role in <!–StartFragment –>supporting the growth and sustainability of MSMEs amidst increasingly competitive markets.<!–EndFragment –> <!–EndFragment –>